The Cross and the Ballot : Catholic Political Parties in Germany, Switzerland, Austria, Belgium and the Netherlands, 1785-1985 - Evans, Ellen Lovell (European History and Culture - Book Archive pre-2000., 1999)
The Cross and the Ballot describes the origins, development and present status of Catholic political parties in Germany, Austria, Switzerland, Belgium and The Netherlands. Its comparative perspective contributes significantly to the current debate over Germany's Sonderweg , that is, whether or not German history has taken a "special path", or unique direction from others. The emergence of a separate political representation for German Catholics was not a deviation from the usual European spectrum but on the contrary was strikingly similar to events in the other four countries. Both the similarities and some notable differences serve to illuminate important aspects of German history.